Circulating and tissue IMP3 levels are correlated with poor survival in renal cell carcinoma. Issue 2 (31st January 2019) - Tschirdewahn, Stephan; Panic, Andrej; Püllen, Lukas; Harke, Nina N.; Hadaschik, Boris; Riesz, Peter; Horváth, Andras; Szalontai, Janos; Nyirády, Peter; Baba, Hideo A.; Reis, Henning; Szarvas, Tibor
Abstract : Tissue protein expression of IMP3 is emerging as a promising prognostic factor in renal cell carcinoma (RCC). The most commonly used immunohistochemical (IHC) antibody has been criticized for its low specificity. In addition, blood levels of IMP3 have not yet been analyzed in RCC. Therefore, we compared the prognostic performance of two different IMP3 IHC antibodies and assessed the prognostic relevance of IMP3 plasma levels in RCC. IMP3 levels were assessed in an overall number of 425 RCC (344× clear cell [ccRCC], 63× papillary [pRCC], 18× chromophobe [chRCC]) patients in three partly overlapping cohorts. Plasma IMP3 concentrations were determined by ELISA in 98 RCC (79× ccRCC, 15× pRCC, 4× chRCC) patients and 20 controls. IMP3 mRNA expression levels were analyzed in 73 frozen tissue samples (55× ccRCC, 12× pRCC, 6× chRCC), while protein expressions were assessed in 366 FFPE samples (294× ccRCC, 56× pRCC, 16× chRCC) using the M3626 and N‐19 antibodies. IMP3 plasma and mRNA expression levels were significantly higher in patients compared to controls and in high‐grade compared to low‐grade tumors. In addition, IMP3 plasma and tissue protein levels (by M3626) were higher and IMP3 mRNA expression levels tended to be higher in patients with distant metastasis. Multivariate analyses in clear cell RCC revealed high IMP3 plasma concentration and mRNA expression as independent predictors of disease‐specific survival. IMP3 immunostainings by M3626 but not by N‐19 were independently associated with poor overall and disease‐specific survival. High plasma and tissue levels of IMP3 are independently associated with poor RCC prognosis. The applied antibody significantly impacts the prognostic performance of analysis. IMP3 analysis may improve risk‐stratification of RCC patients and therefore could help to optimize therapeutic and follow‐up decisions. Abstract : What's new? Current techniques are unable to predict which renal‐cell carcinoma (RCC) patients will develop recurrence or metastasis after surgery. While tissue expression of IMP3 is a promising prognostic factor and therapeutic target in RCC, it requires invasive sampling. In this study, the authors found that preoperative circulating IMP3 levels are independently associated with poor survival in RCC. In addition, they found that the anti‐IMP3 antibody M3626 is superior to N‐19 in terms of prognostic performance. This approach may improve risk‐stratification of RCC patients, and could therefore help to optimize therapeutic planning and follow‐up.